2016
DOI: 10.4142/jvs.2016.17.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autologous platelet-rich plasma application on cutaneous wound healing in dogs

Abstract: This study was conducted to identify the effectiveness of platelet-rich plasma (PRP) and efficacy of intralesional injection as a method of application to acute cutaneous wounds in dogs. Healthy adult beagles (n = 3) were used in this study. Autologous PRP was separated from anticoagulant treated whole blood in three dogs. Cutaneous wounds were created and then treated by intralesional injection of PRP in the experimental group, while they were treated with saline in the control group on days 0, 2 and 4. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 31 publications
10
73
0
Order By: Relevance
“…Furthermore a significant decrease of expression caspase reaction in the cytoplasm of buccal epithelial cells, while a significant increase of expression PCNA immunostaining of these cells as compared with group II. These results were an identity with previous researchers [12,17,[32][33][34], who stated that PRP promotes healing in a different form of lesions because it has many important bioactive proteins hastens the endothelial, mesenchymal, epithelial and epidermal Intralesional injection of PRP was proceeded as it offers a selective spreading in the targeted parts of the wound that require more aid in the healing process and therefore a reduction in the required volume of PRP [35]. Both recent experimental and clinical studies [11,17] have revealed that intralesional injection of PRP in wound healing and muscle injuries lead to better regeneration, increasing neovascularization, reducing fibrosis and scarring.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore a significant decrease of expression caspase reaction in the cytoplasm of buccal epithelial cells, while a significant increase of expression PCNA immunostaining of these cells as compared with group II. These results were an identity with previous researchers [12,17,[32][33][34], who stated that PRP promotes healing in a different form of lesions because it has many important bioactive proteins hastens the endothelial, mesenchymal, epithelial and epidermal Intralesional injection of PRP was proceeded as it offers a selective spreading in the targeted parts of the wound that require more aid in the healing process and therefore a reduction in the required volume of PRP [35]. Both recent experimental and clinical studies [11,17] have revealed that intralesional injection of PRP in wound healing and muscle injuries lead to better regeneration, increasing neovascularization, reducing fibrosis and scarring.…”
Section: Discussionsupporting
confidence: 68%
“…Both recent experimental and clinical studies [11,17] have revealed that intralesional injection of PRP in wound healing and muscle injuries lead to better regeneration, increasing neovascularization, reducing fibrosis and scarring. Previous related studies [35][36][37] had proved that the therapeutic value of PRP in mainly due to high platelet count. Platelets are stimulated by exposure to injured tissues leading to commencement of the coagulation process, which are the onset of the platelets role in healing.…”
Section: Discussionmentioning
confidence: 99%
“…PRP-treated groups showed a high significant increase in the number of CD34 positive endothelial cells lining the newly formed blood vessels when compared with the untreated groups which was more evident at 7 days of injury, consistent with Hicks et al (2016) [60] and Jee et al (2016) [66] . Mammoto et al (2016) [67] reported that PRP accelerates lung regeneration since it contains abundant angiopoietin-1 which stimulates new blood vessels formation, maintains vascular integrity in vitro and in vivo and increases phosphorylation levels of lowdensity lipoprotein receptor-related protein 5 (LRP5) and thus activates angiogenic factor receptor Tie2 in endothelial cells (ECs) and accelerates endothelial cell sprouting.…”
Section: Additionally Wright Carpenter Et Al(2004)supporting
confidence: 85%
“…Some of the results from treatment of chronic wounds with PRP [107109] are similar to those we have discussed in relation to local application of rFXIII in CVLU [95]. Thus far, there have been no reports, at least to our knowledge, about the FXIII-A content of PRP or its contribution to the effects of PRP.…”
Section: Future Perspectives For Fxiii-a In the Field Of Dermatologysupporting
confidence: 67%